Capital Ideas : The IMF and the Rise of Financial Liberalization - Chwieroth, Jeffrey M., 1975- (Book collections on Project MUSE., 2010)
In this work, Jeffrey Chwieroth explores the inner workings of the IMF to understand how it staff's thinking about capital controls changed so radically. In doing so, he also provides an important case study of how international organizations work and evolve.